DEVELOPING BUSINESS ENGLISH AND MANAGEMENT STUDENTSâ READING COMPREHENSION BY USING CONTEXT CLUES - Wulandari, Fariska; Sujadi, Juliana (Edukasi: Jurnal Pendidikan, 2017)
This study was purposed to develop the studentsâ reading comprehension of D class students of second semester ofEnglish Department of Business English and Management Concentration,Polytechnic of TonggakEquatorin academic year 2016-2017. This classroom action research was conducted in two cycles. Field note and test were employed to collect the data. The test consisted of pre-test and progress test. The data of the studentsâ pre-test and progress test score were analyzed to get mean score and the data of observation was analyzed descriptively. Based on the analysis, it was found that the studentsâ reading comprehension developed from pre-test to progress test from cycle to cycle. The mean score of the studentsâ pre-test was 44.1 and then that of the studentsâ progress test in the first and the second cycle were 48,9 and 77,2 respectively. Finally, it can be concluded that the action hypothesis was proved in that context clues developed the studentsâ reading comprehension of D class second semester students of English Department of Business English and Management Concentration, Polytechnic of Tonggak Equator Pontianak in academic year 2016-2017.Keywords: reading comprehension, context clues, classroom action research.